Wireless smoke detection system - Khalifa, Othman Omran; Albagul, Abdulgani; Khan, Sheroz; Islam, Mohd Rafiqul; Usman, Noruzaihan Mod (2008)
This paper attempts to integrate RF technology into smoke detector circuitry.In the proposed system, a smoke detector upon senses smoke activates its alarm, sends a low voltage signal to all other smoke detectors in the vicinity. This low voltage signal activates the individual relays in the other smoke detectors causing them to emit a tone that alerts residents that one of the smoke detectors senses smoke. In this system the transmitter and receiver are installed in a unit and the need for a base is eliminated. The individual smoke detectors are equipped with all the electronics required to both send and receive signals. They are battery operated and therefore they require no external connections. They can be installed by a homeowner just as they would a normal smoke detector. The proposed design is aiming to have Cost efficient system, Compact design,easily expandable, Simple to install, Replaceable components. The system was tested indoor and outdoor with different distance and with the presence of noise.